1999
DOI: 10.1034/j.1398-9995.1999.00303.x
|View full text |Cite
|
Sign up to set email alerts
|

Different serum soluble Fas levels in patients with allergic rhinitis and bronchial asthma

Abstract: Our results suggest a different pathogenesis for allergic rhinitis and bronchial asthma at the cell apoptosis-linked step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 15 publications
3
11
0
Order By: Relevance
“…In this study, we demonstrated significantly lower serum sFas in allergic asthmatic patients as compared to nonatopic subjects. Our observation is line with previous study of Kato et al 27 who described lower levels of serum sFas in patients with symptomatic allergic rhinitis as compared to healthy persons. Jayaraman S, et al 28 observed, that asthmatic subjects had 23% lower levels of Fas + T cells (in the airway mucosa) during treatment with glucocorticoids and suggested that selective resistance to Fas-dependent apoptosis may reflect altered antigen-driven, accessory celldependent signaling.…”
Section: Discussionsupporting
confidence: 95%
“…In this study, we demonstrated significantly lower serum sFas in allergic asthmatic patients as compared to nonatopic subjects. Our observation is line with previous study of Kato et al 27 who described lower levels of serum sFas in patients with symptomatic allergic rhinitis as compared to healthy persons. Jayaraman S, et al 28 observed, that asthmatic subjects had 23% lower levels of Fas + T cells (in the airway mucosa) during treatment with glucocorticoids and suggested that selective resistance to Fas-dependent apoptosis may reflect altered antigen-driven, accessory celldependent signaling.…”
Section: Discussionsupporting
confidence: 95%
“…In contrast, serum sFas levels in patients with bronchial asthma are increased during the attack phase. 32 These findings, together with our observations, indicate that serum sFas concentration is an unpredictable marker in allergic or other hypersensitive diseases, but it is a potential indicator of immunologic activation in CD.…”
Section: Discussionsupporting
confidence: 56%
“…Contradictory observations exist concerning the concentration of serum soluble Fas and FasL (sFas and sFasL) in patients with allergic rhinitis and bronchial asthma [5,6].…”
Section: Introductionmentioning
confidence: 99%